2010
DOI: 10.1038/aps.2010.188
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain facilitates cardiac differentiation of mouse embryonic stem cells through ERK1/2 pathway

Abstract: Aim: To investigate the effects of the cardiotonic steroid, ouabain, on cardiac differentiation of murine embyronic stem cells (mESCs). Methods: Cardiac differentiation of murine ESCs was enhanced by standard hanging drop method in the presence of ouabain (20 µmol/L) for 7 d. The dissociated ES derived cardiomyocytes were examined by flow cytometry, RT-PCR and confocal calcium imaging. Results: Compared with control, mESCs treated with ouabain (20 µmol/L) yielded a significantly higher percentage of cardiomyoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…In our system, puerarin treatment harvested about 7% more α-actinin-positive CMs derived from D3 murine ES cells at day 12 of differentiation compared with control group. Comparable with our report, Yee-Ki Lee et al found that ouabain facilitates cardiac differentiation with a 7% increase in the percentage of cardiac troponin I (cTnl)-positve CMs derived from D3 murine ES cells at day 9 of differentiation [9]. However, Wiese et al reported that suramin has no effect on the percentage of cTnI-positive CMs derived from R1 murine ES cells at day 9 of differentiation, but increases the number of cTnI-positive CMs by 5.6 fold at day 22 [10].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our system, puerarin treatment harvested about 7% more α-actinin-positive CMs derived from D3 murine ES cells at day 12 of differentiation compared with control group. Comparable with our report, Yee-Ki Lee et al found that ouabain facilitates cardiac differentiation with a 7% increase in the percentage of cardiac troponin I (cTnl)-positve CMs derived from D3 murine ES cells at day 9 of differentiation [9]. However, Wiese et al reported that suramin has no effect on the percentage of cTnI-positive CMs derived from R1 murine ES cells at day 9 of differentiation, but increases the number of cTnI-positive CMs by 5.6 fold at day 22 [10].…”
Section: Discussionsupporting
confidence: 87%
“…So far, proteins from TGFβ, BMP, and Wnt families [4,5,6], cytokines [7], natural or synthetic chemical compounds [3,8,9,10,11]; and several transgenic ES cell systems [12] have been applied to selectively enhance the efficiency of cardiac differentiation from ES cells. Among these reports, retinoic acid and transgenic ES cell system are highlighted by their effects on ventricular specialization of ES cells.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the ERK1/2 and NF-κB signaling pathways play a pivotal role in many cellular processes, such as proliferation, apoptosis, and differentiation [24][25][26][27] . PAR2 activation induced by the TF/factor VIIa complex can trigger cell signal transduction through different pathways, including ERK1/2 and NF-κB [15,28] .…”
Section: Discussionmentioning
confidence: 99%
“…Since cardiotonic steroids (CTS) have been reported to regulate ESC differentiation through Na/K-ATPase-related signaling pathways (Lee et al, 2011), we reasoned that CTS may also affect the differentiation of adult stem cells such as, BMSCs. The above mentioned P3 BMSCs were used to test whether MBG, a specific ligand of Na/K-ATPase, regulates BMSCs differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports demonstrated Na/K-ATPase expression in undifferentiated embryonic stem cells (ESCs) as well as in ESC-derived cardiomyocytes (Otsu et al, 2005). CTS such as ouabain promote differentiation of ESCs into cardiac myocytes through an extracellular regulated kinase (ERK) signaling pathway (Lee et al, 2011). This study evaluated whether CTS-induced Na/K-ATPase signaling regulates differentiation in BMSCs.…”
Section: Introductionmentioning
confidence: 99%